2017 IEEE International Conference on Computer Vision Workshops (ICCVW) 2017
DOI: 10.1109/iccvw.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

3D Object Reconstruction from a Single Depth View with Adversarial Learning

Abstract: Recent advancements in deep learning opened new opportunities for learning a high-quality 3D model from a single 2D image given sufficient training on large-scale data sets. However, the significant imbalance between available amount of images and 3D models, and the limited availability of labeled 2D image data (i.e. manually annotated pairs between images and their corresponding 3D models), severely impacts the training of most supervised deep learning methods in practice. In this paper, driven by a novel des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 45 publications
0
125
0
Order By: Relevance
“…Recently, there are some inspiring works in applying GAN to 3D shape processing. Most of them focus on generating 3D objects either from a probabilistic space [32] or from 2D images [36,11,27]. Moreover, Wang et al [30] introduced a 3D-ED-GAN for shape completion given a corrupted 3D scan as input.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, there are some inspiring works in applying GAN to 3D shape processing. Most of them focus on generating 3D objects either from a probabilistic space [32] or from 2D images [36,11,27]. Moreover, Wang et al [30] introduced a 3D-ED-GAN for shape completion given a corrupted 3D scan as input.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of 3D reconstruction, the encoder can be a ConvNet/ResNet [42], [99] or a variational autoencoder (VAE) [17]. The generator decodes the latent vector x into a 3D shape X = g(x).…”
Section: Adversarial Trainingmentioning
confidence: 99%
“…Central to GAN is the adversarial loss function used to jointly train the discriminator and the generator. Here x = h(I) where I is the 2D images(s) of the training shape X. Yang et al [42], [99] observed that the original GAN loss function presents an overall loss for both real and fake input. They then proposed to use the WGAN-GP loss [100], [101], which separately represents the loss for generating fake reconstruction pairs and the loss for discriminating fake and real construction pairs, see [100], [101] for the details.…”
Section: Adversarial Trainingmentioning
confidence: 99%
“…Instead of augmenting depth maps another option would be to infer depth information directly in the 3D map. [20] generalizes residual networks to infer complete 3D object shapes from single view depth images, an interesting approach as it bridges 2D and 3D depth/shape completion. A fully three dimensional multi-modal network proposed in [21] is capable of completing a partial 3D occupancy grid while providing per-voxel semantic information.…”
Section: A Inference Of 3d Structurementioning
confidence: 99%